NECAB1-3, parvalbumin, calbindin, and calretinin in the hippocampus of the European mole - Maliković, Jovana; Amrein, Irmgard; Vinciguerra, Lorenzo; Wolfer, David P.; Slomianka, Lutz (Frontiers in Neuroanatomy, 2024)
Many calcium-binding proteins are expressed in a region-and cell-type specific manner in the mammalian hippocampus. Neuronal calcium-binding proteins (NECABs) are also expressed in hippocampal neurons, but few species have been investigated, with partly controversial findings. We here describe NECAB1, NECAB2 and NECAB3 as well as parvalbumin, calbindin, and calretinin in the European mole, and compare staining patterns of these proteins with those in mouse and other species. While subtle differences are present, NECAB staining in the European mole was generally similar to those in mouse. Common to European moles, mice, and other species we investigated, large hilar polymorphic cells, likely to represent mossy cells, were positive for all three NECABs. NECAB1 and 2 are suitable as markers for these cells along the entire septotemporal axis of the hippocampus. In the European mole, parvalbumin, calbindin and calretinin showed traits that have been described in other species before, albeit in a unique combination. In summary, we provide the first description of distribution of these proteins in the hippocampus of the European mole. This subterranean, insectivorous, and solitary living species belongs to the Order of Eulipotyphla. Despite many similarities with other subterranean species from the rodent order in terms of lifestyle, its hippocampus is cytoarchitecturally much more elaborated than in, e.g., mole-rats. It remains an open question if the hippocampal structure of the European mole reflects evolutionary constraints or ecology. Our descriptive study highlights the diversity in hippocampal cytoarchitecture even in small mammalian species.